Ultrasensitive melanoma biomarker detection using a microchip SERS immunoassay with anisotropic Au–Ag alloy nanoboxes. Issue 48 (4th August 2020) - Kumar, Aswin Raj; Shanmugasundaram, Karthik Balaji; Li, Junrong; Zhang, Zhen; Ibn Sina, Abu Ali; Wuethrich, Alain; Trau, Matt
Abstract : The detection of circulating biomarkers in liquid biopsies has the potential to provide a non-invasive route for earlier cancer diagnosis and treatment management. Abstract : The detection of circulating biomarkers in liquid biopsies has the potential to provide a non-invasive route for earlier cancer diagnosis and treatment management. Melanoma chondroitin sulfate proteoglycan (MCSP) is a membrane protein characteristic for melanoma cell migration and tissue invasion with its soluble form (sMCSP) serving as a potential promising diagnostic surrogate. However, at the initial disease stage, the detection of sMCSP is challenging because of its low abundance and the required high specificity to analyze sMCSP in complex bodily fluids. Herein, we report a highly sensitive and high-throughput microchip that enables Surface Enhanced Raman Spectroscopy (SERS) immunoassay for parallel detection of up to 28 samples. Key to assay speed and sensitivity is the stimulation of an alternating current-induced nanofluidic mixing that improves target-sensor collision and displacement of non-specific molecules. Anisotropic Au–Ag alloy nanoboxes (NB's) with strong plasmonic hot spots provide single SERS particle sensitivity that enables ultrasensitive sMCSP detection of as low as 0.79 pM (200 pg ml −1 ). As a proof of concept study, we investigate the assay performance in simulated melanoma patient samples.